Level of knowledge of adolescents about HIV infection: A relationship with self-care and risk behaviors - Silva, Natanias Macson da (2022)
Introduction: Adolescence is marked by biopsychosocial and behavioral changes important for the construction of autonomy during new experiences. However, some habits during this phase may pose risk to HIV infection. Objective: To evaluate the adolescents' practices that may pose a risk to HIV infection, contrasting behavioral aspects with the level of prior knowledge about this infection. Methods: This is a cross-sectional study with descriptive, quantitative and correlational approaches applied to 273 adolescents from public educational institutions in six Brazilian municipalities. The data were collected through two questionnaires which focused on self-care and the level of knowledge about anatomy, pathophysiology and risk factors of HIV infection. Absolute and relative frequency measures were used, as well as Pearson correlation tests (p value < 0.05).  Results: There was a higher representativeness of 16-17 years-old and female school adolescents. The results showed risk behaviors for HIV exposure such as early sexual activity (38.4%), drug use (21.8%), multiple sexual partners (40.4%) and unprotected sex (54.5%); this was a scenario that was not necessarily related to the lack of knowledge. Notwithstanding, the study points out that the earlier the debut sexual activities or drug use, the greater the number of sexual partners during adolescence, suggesting a high risk of HIV infection. In regards to the use of interactive methodologies, these presented themselves as potential tools in permanent health education. Conclusion: The study verified the important risk behaviors related to HIV infection by school adolescents, and also that these practices are not necessarily linked to the lack of knowledge about this issue. The implications of this study are directed towards the promotion of changes in practices of health and education professionals, as well as the development of public policies aimed at reducing the adolescents’ risk behaviors.